Isolation of bacteria capable of degrading organophosphate flame retardants - Nguyen, Thị Lan Anh; Pham, Thi Phuong; Tran, Thi Thu Hien; Phung, Duc Hieu; Tran, Thi Thu Lan; Dao, Hai Yen (Vietnam Journal of Science and Technology, 2024)
Wastewater samples from To Lich River contaminated with organophosphate flame retardant (OPFRs) were collected and enriched in a medium supplemented with OPFR compounds. As a result, 10 bacterial strains were isolated and identified based on 16S rRNA gene sequence analysis. These bacterial strains belong to the genera Achromobacter, Pseudomonas, Bordetella, and Rhizobium. All 10 bacterial strains exhibited the ability to degrade some OPFR compounds, but only two strains, Achromobacter sp. BWTL6 and Rhizobium sp. BWTL7, effectively degraded all 5 tested OPFR compounds. These two bacterial strains demonstrated the capability to degrade more than 70% of tris(1,3-dichloro-2-propyl)phosphate (TDCPP) (at 10 mg/L concentration) within 7 days. Furthermore, both Achromobacter sp. BWTL6 and Rhizobium sp. BWTL7 were able to utilize tris(2-chloroethyl) phosphate (TCEP), triethyl phosphate (TEP), tris(2-butoxyethyl) phosphate (TBEP), and trimethyl phosphate (TMP) for growth, exhibiting clear cell proliferation and OPFR removal rates ranging from 40 to 58%. In addition, bacterial strain Bordetella sp. BWTL3 degraded 61.5% of TDCPP and 97.7% of TBEP after 7 days of culture. In this study, all three bacterial strains belonging to the Achromobacter, Rhizobium and Bordetella are potential candidates for remediation of environments contaminated with OPFRs.